THE EFFECT OF DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE OF PT INDOFOOD CBP SUKSES MAKMUR TBK PEKANBARU BRANCH - R. Rudi Alhempi; Saiful Anuar; Elvi Lastriani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The research was conducted on PT Indofood CBP Sukses Makmur Tbk Cabang Pekanbaru that aimed to figure out the impact of discipline and motivation on performance of employees, either simultaneously or partially. The population of the research was all of the employees of the PT Indofood CBP Sukses Makmur Tbk Cabang Pekanbaru. Total sample of 80 respondents on PT Indofood CBP Sukses Makmur Tbk Cabang Pekanbaru. The sampling technique used is simple random side and multiple linier regression analysis method by using SPSS Version 20. Simultaneous regression (F test) showed that the independent variables studied (work discipline and work motivation) together (simultaneously) have a significant influence on the dependent variable (performance of employee). Partial test (t test) shows, the independent variables have a significant effect on performance of employees. There is a high contribution of the variable discipline and motivation on the performance of employees in PT Indofood CBP Sukses Makmur Tbk Cabang Pekanbaru, the illustrated by the coefficient of determination obtained. Keywords: discipline, motivation, performance of employee